2018
DOI: 10.1111/liv.13686
|View full text |Cite
|
Sign up to set email alerts
|

Primary Biliary Cholangitis in British Columbia First Nations: Clinical features and discovery of novel genetic susceptibility loci

Abstract: Our whole genome linkage study results reflect the multifactorial nature of Primary Biliary Cholangitis, support previous studies suggesting signalling pathway involvement and identify new candidate genes for consideration.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(30 citation statements)
references
References 51 publications
0
30
0
Order By: Relevance
“…In this study, the linkage analysis identified no loci meeting the a priori criteria for significance, a result that may relate to the small sample size . However, loci yielding LOD scores greater than 2.0 were identified at chromosomal regions 1q23‐q24, 6q21, 9q21, 17p13 and 19p13.…”
mentioning
confidence: 66%
See 4 more Smart Citations
“…In this study, the linkage analysis identified no loci meeting the a priori criteria for significance, a result that may relate to the small sample size . However, loci yielding LOD scores greater than 2.0 were identified at chromosomal regions 1q23‐q24, 6q21, 9q21, 17p13 and 19p13.…”
mentioning
confidence: 66%
“…However, their subsequent fate was clearly influenced by early colonists from Europe, who introduced many In this issue, Asuri and colleagues report their findings from a whole genome linkage analysis of 32 FN families from coastal British Columbia. 4 They studied 44 FN patients suffering from PBC and 61 unaffected relatives with the aim of identifying candidate genes involved in PBC susceptibility. Notably, there was a high prevalence of autoimmune disease in both FN cases and controls, with 50% of the PBC patients having a coexisting autoimmune disease such as RA (23%) and SLE (9%).…”
Section: New Perspectives On the Complexity Of Genetic Predispositionmentioning
confidence: 99%
See 3 more Smart Citations